Antiviral treatment for COVID-19 in Peru: Beyong the 2magic use" of ivermectin - Gonzales-Zamora, José A. (2022)
Since the beginning of the pandemic, drugs with no scientific evidence for COVID-19, such as ivermectin, have been used in Peru. Despite its proven ineffectiveness and the catastrophic consequences of its implementation, ivermectin is still recommended in some medical centers in the country. In the rest of the world, the advance in antiviral treatment has been enormous. In this context, we can highlight the use of remdesivir, which is the only antiviral for COVID-19 with full FDA approval that is recommended in hospitalized patients with severe disease; however, the scientific evidence also suggests that it is very useful in high-risk individuals with a mild COVID-19 presentation. Other important therapies are the monoclonal antibodies, which are prescribed for outpatients with mild or moderate symptoms. They are also used in prevention, particularly in pre- and post-exposure prophylaxis. One of the greatest advances has been the development of antivirals of oral administration, such as molnupiravir and paxlovid, which have been recently authorized by the FDA. Unfortunately, these therapies are not available in Peru, which is a concerning scenario specially with the advent of the third COVID-19 wave.